Irritant bullous contact dermatitis caused by a rove beetle: An illustrated clinical course. (20th February 2012) - McGrath, Lindsay; Piliouras, Peter; Robertson, Ivan
ABSTRACT A 26‐year‐old Australian female traveller in Sierra Leone presented with an irritant bullous contact dermatitis consistent with paederus dermatitis. The lesions were treated with a potent topical corticosteroid with good effect. The affected area resolved in 6 weeks and hyperpigmention persisted for months until complete resolution. This dermatitis occurs when beetles of the genus Paederus (rove beetles) are crushed on the skin, releasing pederin. The same dermatitis ensues with Australian Paederus species. Serial clinical photographs are presented which will aid Australian dermatologists in the diagnosis of this dermatitis, which presents in regional Australian patients and returned overseas travellers.